ASEAN vs. WTO DSM: Overcoming Jurisdiction Issues to Encourage Regional Trade Agreements’ System Efficacy - Wisawawit Udomjitpittaya; Zuhda Mila Fitriana (Universitas Airlangga, 2019)
Dispute settlement mechanism holds an important role in upholding the rights and obligations of member countries under any agreements signed by ASEAN members as well as to resolve any dispute between Members, therefore, AFTA has its own dispute settlement procedure. Unfortunately, it has not been fully efficient to solve the trade dispute within ASEAN countries because the parties tend to bring their disputes to WTO Dispute Settlement Body (DSB). This is because there are some issues and constraints in the AFTA DSM which vary from technical issues to cultural issues. Specifically, although there has not been any overlap issue with the WTO, the AFTA DSM might have the possibility to create such issue due to the lack of efficieny in the legal framework. It also has another major issues such as difficult access for private parties to defend their rights and the disputes in AFTA are rarely resolved because of the ‘ASEAN Way’ method. The ongoing reliance of ASEAN Member States to WTO DSB is an unfortunate situation knowing the fact that the WTO DSB has been struggling with overlap jurisdiction issues with other RTAs throughout the years. The aims of this writing is proposing possible solutions to encourage the efficacy of RTA’s DSB usage particularly in ASEAN Region.